Prediction of Distant Educational Goals by Goals in Other Domains and Perceived Contextual Opportunities - Kolesovs, Aleksandrs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Lifelong learning is linked to successful economic participation. At the same time, individual activities are framed by contextual opportunities for education and occupation.This study explored personal and contextual factors predicting choice of education as a distant goal among emerging adults. Research participants were 120 emerging adults aged from 20 to 30 living in Riga (62% offemales).The participants evaluated to what extent their near and distant goals associate with different life domains and reported perceived opportunities for fulfillment of these goals provided by their living place. Distant goals in the educational domain were positively predicted by current educational, distant occupational, and self-related goals, and negatively predicted by higher perceived opportunities provided by their living place. The last finding indicates an association of a perceived lack of opportunities in the local context with a need for planning the further education.